Crossing: how we label and react to people on the move - Hamlin, Rebecca (Stanford University Press, 2021)
The migrant/refugee binary -- Uneven sovereignties -- Academic study -- The United Nations High Commissioner for Refugees -- The Global South -- Arrivals in Europe -- American public discourse -- Beyond binary thinking.